Athletics, gymnastics, and agōn in Plato - Reid, Heather Lynne, 1963-; Ralkowski, Mark; Zoller, Coleen P., 1976- (Parnassos Press, 2020)
"In the Panathenaic Games, there was a torch race for teams of ephebes that started from the altars of Eros and Prometheus at Plato's Academy and finished on the Acropolis at the altar of Athena, goddess of wisdom. It was competitive, yes, but it was also sacred, aimed at a noble goal. To win, you needed to cooperate with your teammates and keep the delicate flame alive as you ran up the hill. Likewise, Plato's philosophy combines competition and cooperation in pursuit of the goal of wisdom. On one level, agonism in Plato is explicit: he taught in a gymnasium and featured gymnastic training in his educational theory. On another level, it is mimetic: Socratic dialogue resembles intellectual wrestling. On a third level, it is metaphorical: the athlete's struggle illustrates the struggle to be morally good. And at its highest level, it is divine: the human soul is a chariot that races toward heaven. This volume explores agonism in Plato on all of these levels, inviting the reader--as Plato does--to engage in the megas agōn of life. Once in the contest, as Plato's Socrates says, we're allowed no excuses."--